Neuropathological findings in COVID-19 vs. non-COVID-19 acute respiratory distress syndrome—A case-control study - Humayun, Mariyam; Zhang, Lucy; Zaikos, Thomas D.; Kannapadi, Nivedha; Suarez, Jose I.; Hager, David N.; Troncoso, Juan C.; Cho, Sung-Min (Frontiers in Neurology, 2023)
Acute brain injury (ABI) and neuroinflammation is reported in COVID-19 and acute respiratory distress syndrome (ARDS). It remains unclear if COVID-19 plays an independent role in development of ABI compared to those with non-COVID-19 ARDS. We aimed to evaluate if COVID-19 ARDS is associated with higher risk and specific patterns of ABI compared to non-COVID-19 ARDS. We conducted an age and sex matched case-control autopsy study at a tertiary academic center. Ten patients with COVID-19 ARDS were matched to 20 non-COVID-19 ARDS patients. Baseline demographics were comparable between the two groups including severity of ARDS (p = 0.3). The frequency of overall ABI (70 vs. 60%), infratentorial ABI (40 vs. 25%), ischemic infarct (40 vs. 25%), intracranial hemorrhage (30 vs. 35%), and hypoxic-ischemic brain injury (30 vs. 35%) was similar between COVID-19 and non-COVID-19 ARDS patients, respectively (p > 0.05). Intracapillary megakaryocytes were exclusively seen in 30% of COVID-19 patients. Overall, frequency and pattern of ABI in COVID-19 ARDS was comparable to non-COVID-19.